Improving the psychophysiological condition of secondary school learners through the Olympic education program during the Covid-19 pandemic - Galan, Yaroslav; Moseychuk, Yuriy; Dutchak, Yurii; Korolianchuk, Andrii; Yeremiia, Yana; Yarmak, Olena; Kurnyshev, Yurii; Duditska, Svitlana; Hauriak, Olena; Beshlei, Olga (My University, 2023)
The article aims to evaluate the impact of the proposed "Olympic Education" program on the physical and psychoemotional state of middle school children. Materials and methods. We conducted research in Chernivtsi specialized schools, and 34 children aged 13-14 participated in the experiments. We tested effectiveness experimentally. A group of 16 boys and 18 girls were involved in the extracurricular activities based on the proposed program. Results. The results of the transformative experiment proved that implementation of the innovative program contributed to a significant increase in the indicators referring to the physical and psycho-emotional state of children aged 13-14. Using a large arsenal of mobile games and online activities contributed to probable changes (р<0.05; р<0.001) in the indicators characterizing the respiratory system, particularly the breath retention time on inhalation and exhalation increased in both groups. Implementing the Olympic education program contributed to a probable (p<0.05; p<0.001) improvement of the vast majority of volitional qualities in both groups. Conclusions. The results obtained during the pedagogical experiment testify to the effectiveness of the innovative Olympic education program in improving the physical and psycho-emotional state of secondary school children.
Keywords: Olympic Education; Covid-19; online learning; secondary school learners; Physical Education; psychophysiological condition